International Graduate Students’ Challenges and Learning Experiences in Online Classes - Karkar-Esperat, Tala Michelle (Journal of International Students, 2018)
The purpose of this case study was to identify the learning experiences and examine the challenges facing three international graduate students enrolled in online, asynchronous classes in an American public university. Applying the lens of constructivism, data were collected from a questionnaire, semi-structured interviews, and a focus group. Findings from the study indicate that the students faced challenges with English language proficiency, isolation, instructor’s lack of experience, and a lack of motivation to study in online classes. Notwithstanding, students described flexibility and convenience as key factors of the learning experiences in a virtual classroom. Implications for administrators and course designers in understanding student perspectives of online classes and best practices for conducting asynchronous classes are provided.